AGRESIVITAS DAN DINAMIKA POPULASI KUNJUNGAN SERANGGA PENYERBUK Elaeidobius kamerunicus Faust. (Coleoptera : Curculionidae) PADA BUNGA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI KEBUN GREA PT. KARYA HEVEA INDONESIA BANGUN PURBA SUMATERA UTARA - Muhammad Yusuf Dibisono; Guntoro Guntoro; Widia Lista Nasution (Jurnal Agro Estate, 2017)
Elaeidobius kamerunicus is one of the weevil pollinator of oil palm. Weevil pollinator, E. kamerunicus in plantation is useful to increase fruit set. Continuity of the oil palm pollination require minimal amount of the weevil. This research to know aggressiveness and population dynamic of the weevil E. kamerunicus in ﬂower of oil palm at Grea Estate PT. Karya Hevea Indonesia. This research uses descriptive analysis method consists of observing and collecting data about the aggressiveness and population dynamics of weevil pollinators visit in anthesis male ﬂowers and receptive female ﬂowers of oil palm of seven years after planting. Observations were made on an hourly basis, starting at 08:00 am until 15:00 pm. Observations were made daily on trees with receptive ﬂowers and anthesis ﬂowers, carried out for 20 days with a different tree every day. The results showed that the aggressiveness of the weevil Elaeidobius kamerunicus as the main oil palm pollinating insect had a signiﬁcant difference in interest. Where E. kamerunicus tend to be more aggressive to visit the male ﬂower anthesis as many as 1399 tails of the visiting receptive female ﬂower that only 25 tails. Effect of temperature on the population dynamics of E. kamerunicus visit also differ between male ﬂowers and female ﬂowers. For male ﬂowers, E. kamerunicus is more active at 27 ° C. While in the female ﬂowers, E. kamerunicus is active at 30 ° C. E. kamerunicus actively visited male anthesis ﬂowers and receptive female ﬂowers at 63% and 62% moisture respectively.